2022
DOI: 10.1128/spectrum.00128-22
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Saliva and Midturbinate Swabs for Detection of SARS-CoV-2

Abstract: The findings of this manuscript are increasingly important with new variants that appear to have shorter incubation periods emerging, which may be more prone to detection in saliva before detection in nasal swabs. Therefore, there is an urgent need to provide the science to support the use of a detection method that is highly sensitive and widely acceptable to the public to improve screening rates and early detection.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 34 publications
0
35
2
Order By: Relevance
“…The study did confirm higher antigen concentrations in symptomatic cases compared to asymptomatic and oligosymptomatic cases across all three specimen types, as anticipated given the association between viral carriage and symptom onset. While recent studies suggest that early onset of SARS-CoV-2 can be first observed in the saliva by RT-PCR, 4,5,20 the overall lower antigen levels observed in saliva in this study suggests that current rapid antigen tests are not sensitive enough to leverage this opportunity for earlier infection detection.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…The study did confirm higher antigen concentrations in symptomatic cases compared to asymptomatic and oligosymptomatic cases across all three specimen types, as anticipated given the association between viral carriage and symptom onset. While recent studies suggest that early onset of SARS-CoV-2 can be first observed in the saliva by RT-PCR, 4,5,20 the overall lower antigen levels observed in saliva in this study suggests that current rapid antigen tests are not sensitive enough to leverage this opportunity for earlier infection detection.…”
Section: Discussioncontrasting
confidence: 74%
“…[21][22][23] The study did confirm higher antigen concentrations in symptomatic cases compared to asymptomatic and oligosymptomatic cases across all three specimen types, as anticipated given the association between viral carriage and symptom onset. While recent studies suggest that early onset of SARS-CoV-2 can be first observed in the saliva by RT-PCR, 4,5,20…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also important to note that variation of several patient and personnel factors related to naso-oropharyngeal swabbing introduces iatrogenic preanalytical variability that may adversely affect testing results 17 , 18 . Furthermore, these findings may be useful in light of recent reports suggesting changing patterns of viral shedding, tissue tropism, and transmission mechanics 19 21 , in favor of oral cavity and saliva, depending on the emerging SARS-CoV-2 variant such as Omicron 22 .…”
Section: Discussionmentioning
confidence: 87%